Resistome and virulome study on pathogenic Streptococcus agalactiae Guangzhou-SAG036. (October 2020) - Xu, Zhenbo; Lu, Zerong; Soteyome, Thanapop; Chen, Ling; Liang, Yi; Bai, Caiying; Huang, Tengyi; Liu, Junyan; Harro, Janette M.; Kjellerup, Birthe V.
Abstract: Streptococcus agalactiae is considered as a leading case of bacterial infection among neonates. Although relative protection strategies have been performed in many high-income countries, resulting in a massive reduction in the occurrences of early-onset GBS disease, the late-onset disease has not affected. Here, the whole genome of S. agalactiae Guangzhou-SAG036 was sequenced by the Pacific Biosciences Sequel using the P4–C2 chemistry and the continuous long reads were used for de novo assembly using HGAP. Besides, genes prediction and multiply annotation were performed by comparing it with diverse databases. The whole genome has a length of 2, 206, 504 bp and contains 2162 predicted genes with an average G + C content of 35.85%. Based on the whole genome sequence, 2 large prophages, 20 virulence factors genes, and 8 antibiotic resistant genes were identified. MLST analysis revealed S. agalactiae Guangzhou-SAG036 was identified as ST-17. The virulence factors genes were identified with different functions including adherence, antiphagocytosis, spreading factor, immune evasion, invasion, toxin. Besides, the antibiotic-resistant genes may provide S. agalactiae with resistance to multi-drugs including erythromycin, streptomycin, azithromycin, spiramycin, ampicillin, kanamycin, cationic peptides, and tetracycline. Therefore, the infection of S. agalactiae Guangzhou-SAG036 ST-17 strain maybe caused by the complex virulence factors and multi-drugs resistance. These results contribute to further understand GBS epidemiology and surveillance targets. Highlights: The whole genome of S. agalactiae Guangzhou-SAG036 has a length of 2, 206, 504 bp with an average G + C content of 35.85%. The genome shows high similarity (99% identity) with two sequenced S. agalactiae strains isolated from China in 2016 and one isolated from Canada in 2010. 2162 predicted genes had been identified containing two prophages. MLST type was identified as ST-17. 19 virulence factors genes and 8 antibiotic resistant genes were identified.